Beyond strength: dietary nitrate augments self-selected functional mobility after resistance training in middle-aged adults - Brandon M. Peoples; Mason C. McIntosh; Kenneth D. Harrison; Bria R. Smith; Keven G. Santamaria Guzman; Silvia E. Campos-Vargas; Damaris C. Cifuentes; Breanna J. Mueller; Andreas N. Kavazis; Darren T. Beck; Michael D. Roberts; Jaimie A. Roper (GeroScience, 2025)
This study aimed to assess whether dietary nitrate supplementation with resistance training (RT) augments gait performance and functional mobility in inactive middle-aged and older adults. We hypothesized that combining nitrate-rich beetroot juice (BRJ) with RT would yield improvements in gait and functional mobility compared to RT with nitrate-depleted beetroot juice placebo (PLA) supplementation. In this 12-week, randomized, double-blind, placebo-controlled pilot trial, 28 healthy, inactive adults (56 ± 7 years) were assigned to either a BRJ (~ 12.8 mmol nitrate/day) or PLA group while completing a supervised, full-body RT program (2×/week). Pre- and post-intervention assessments included the instrumented stand and walk (iSAW), 6-min walk test (i6MWT), and timed up and go (iTUG) tests. Supplement adherence, training compliance, and volume were equivalent between groups. ANCOVA analyses controlling baseline values revealed significant between-group differences favoring the BRJ group for gait speed (adjusted means: 1.38 vs 1.27 m/s, p = .010), stride length ( p < .001), and iTUG duration ( p < .05). Within-group analyses confirmed that the BRJ group experienced significant improvements in gait speed ( p < 0.001) and iTUG duration ( p < 0.05), while the PLA group showed no functional changes, indicating that 12 weeks of RT alone was insufficient to improve functional mobility in our sample despite equivalent training responses ( p > .05). In our middle-aged sample, supplementing dietary nitrate alongside RT led to clinically meaningful improvements in functional mobility during self-selected conditions, exceeding the gains from 12 weeks of twice-weekly RT alone. Preliminary descriptive analyses revealed sex-specific group-level differences that might suggest emerging trends. Although no inferential statistics were conducted, the patterns provide potential directions for future research investigating the effects of RT in middle-aged adults. Graphical Abstract

A data-driven index for evaluating BMP water quality performance - Elizabeth A. Fassman-Beck; Edward D. Tiernan; Ka Lun Cheng; Kenneth C. Schiff (Water Research, 2025)

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

Design to monitor trend in abundance and presence of American beaver (Castor canadensis) at the national forest scale - Jeffrey L. Beck; Daniel C. Dauwalter; Kenneth G. Gerow; Gregory D. Hayward (Environmental Monitoring and Assessment, 2010)

Lung-to-lung circulation times during exercise in heart failure - Norman R. Morris; Eric M. Snyder; Kenneth C. Beck; Bruce D. Johnson (European Journal of Applied Physiology, 2009)

Evaluation of cardiac output from a tidally ventilated homogeneous lung model - Habib Benallal; Kenneth C. Beck; Bruce D. Johnson; Thierry Busso (European Journal of Applied Physiology, 2005)